In situ strength assessment of rapid set concrete in real time using resonant peak parameters of embedded PZT transducers - Naveet Kaur; Prateek Negi (Scientific Reports)
Abstract The in-situ concrete strength is estimated using qualitative techniques such as ultrasonic pulse velocity and the Schmidt hammer test, which are challenging to perform at inaccessible locations in large structures. Furthermore, these techniques are only successful in the outside regions of concrete casting and provide no insights for the inside regions. The researchers have been exploring new techniques using Lead Zirconate Titanate (PZT) impedance transducers for monitoring concrete strength at required locations in real-time, to optimise the construction process. However, the existing studies only establish the feasibility of the concept with limited testing and lack considering the effect of field parameters i.e., temperature and relative humidity. The present study discusses a novel technique of monitoring in-situ strength in rapid set concrete, using resonant peak parameters from the Electro-Mechanical Impedance (EMI) signatures of embedded Resin Jacketed Piezo (RJP) sensors. The developed RJP sensors are easy to manufacture and provide signatures within acceptable consistency. Different correlation models have been developed considering the effect of field parameters through extensive testing in controlled lab conditions. Also, the developed technique has been successfully implemented in a real-life bridge construction site. It was observed that there is a clear difference in the in-situ concrete strength achieved in the outer region of the pier of an under-construction bridge in comparison to the inner region. The outcomes of this study will pave in better decision making for the formwork removal in the casting yards and thus help in improving the construction rate keeping safety in concern.